Relasi Korupsi Politik dengan Perilaku Masyarakat dalam Pilkada Riau - Hendrik, Doni; Rahmatunnisa, Mudiyati; Paskarina, Caroline; Alamsah D, Nandang (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2023)
Riau Province is a region that has a high level of corruption among regional heads in Indonesia. Apart from the high level of corruption, community behavior also shows a tendency towards transactional behavior by asking for rewards, assistance and souvenirs from candidates in the regional election process. Likewise, elites and society seem to be breeding grounds for corruption, by asking candidates for donations and various forms of materials and services so that candidates have high costs in the regional election process. This research uses a cultural perspective in analyzing the phenomenon of corruption. The aim of this research is to explain how the behavior of the Riau people in the regional elections is related to the corrupt behavior of regional heads. Using qualitative methods, data collection techniques through in-depth interviews, and informal selection through purposive sampling, research findings were obtained that in the regional election process for the Governor of Riau, there was behavior of the community, figures and elites who tended to be transactional by trying to ask for various kinds of rewards such as money, goods, services. and facilities for candidates in the regional election process. Such behavior is common in Riau and even tends to be